An exemplar model should be able to explain all syntactic priming phenomena: A commentary on Ambridge (2020). Issue 5 (October 2020) - Messenger, Katherine; Hardy, Sophie M.; Coumel, Marion
The authors argue that Ambridge's radical exemplar account of language cannot clearly explain all syntactic priming evidence, such as inverse preference effects ( greater priming for less frequent structures), and the contrast between short-lived lexical boost and long-lived abstract priming. Moreover, without recourse to a level of abstract syntactic structure, Ambridge's account cannot explain abstract priming in amnesia patients or cross-linguistic priming. Instead, the authors argue that abstract representations remain the more parsimonious account for the wide variety of syntactic priming phenomena.